2010
DOI: 10.1080/00071660903573702
|View full text |Cite
|
Sign up to set email alerts
|

Effects of oregano essential oil with or without feed enzymes on growth performance, digestive enzyme, nutrient digestibility, lipid metabolism and immune response of broilers fed on wheat–soybean meal diets

Abstract: 1. The study was conducted to determine the effects of dietary supplementation of enzyme and oregano essential oil at two levels, alone or together, on performance, digestive enzyme, nutrient digestibility, lipid metabolism and immune response of broilers fed on wheat-soybean meal based diets. 2. The following dietary treatments were used from d 0 to 21. Diet 1 (control, CONT): a commercial diet containing no enzyme or oregano essential oil, diet 2 (ENZY): supplemented with enzyme, diet 3 (EO250): supplemented… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
51
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 48 publications
12
51
0
Order By: Relevance
“…In some countries, due to the human health concern on the use of antimicrobial agents and their effects on antimicrobial resistance in humans, certain AGP have already been banned, and there is a possibility of future restrictions on their use worldwide; therefore, non-antibiotic alternatives to control diseases and promote broiler growth, such as organic acids (Vieira et al, 2008), probiotics (Mountzouris et al, 2010), prebiotics (Patterson & Burkholder, 2003), phytogenic additives (Hernández et al, 2004), and essential oils (Basmacioğlu Malayoğlu et al, 2010),are of great interest. The use of phytogenic additives (PA) in poultry feeds has been investigated relative to their stimulation of digestive enzymes (Basmacioğlu Malayoğluet al, 2010), antimicrobial activity (Mitsch et al, 2004), antifungal activity (Gowdaet al, 2004), antiparasitical activity (Giannenas et al, 2003), antioxidant effects (Ciftci et al, 2010;Zhang et al, 2013), and immuno stimulant action (Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In some countries, due to the human health concern on the use of antimicrobial agents and their effects on antimicrobial resistance in humans, certain AGP have already been banned, and there is a possibility of future restrictions on their use worldwide; therefore, non-antibiotic alternatives to control diseases and promote broiler growth, such as organic acids (Vieira et al, 2008), probiotics (Mountzouris et al, 2010), prebiotics (Patterson & Burkholder, 2003), phytogenic additives (Hernández et al, 2004), and essential oils (Basmacioğlu Malayoğlu et al, 2010),are of great interest. The use of phytogenic additives (PA) in poultry feeds has been investigated relative to their stimulation of digestive enzymes (Basmacioğlu Malayoğluet al, 2010), antimicrobial activity (Mitsch et al, 2004), antifungal activity (Gowdaet al, 2004), antiparasitical activity (Giannenas et al, 2003), antioxidant effects (Ciftci et al, 2010;Zhang et al, 2013), and immuno stimulant action (Chen et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic additives have been documented to improve nutrient digestibility in swine (Maenner et al, 2011) and in poultry (Basmacioglu Malayoglu et al, 2010). We think that aromatic additives are often claimed to improve the flavor and palatability of feed, thus increasing voluntary feed intake resulting in improved productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Slominski et al (2004) in a study on 16 different samples of wheat screening showed that NSP content of samples varied from 72 to 118 g/kg with the mean of 100 g/kg. The NSP fraction increases digesta viscosity and protects lipids, starch, and protein, thereby decreasing nutrient digestibility, modifying intestinal microflora in the digestive system, reducing physiological and morphological changes, and depressing the growth performance (Preston et al, 2001;Basmacioglu et al, 2010). The use of NSP-degrading enzymes as dietary supplements, may positively affect poultry health and productivity fed diets containing grains such as wheat, rye, barley and oats (Basmacioglu et al, 2010).…”
Section: Measurementsmentioning
confidence: 99%
“…The use of NSP-degrading enzymes as dietary supplements, may positively affect poultry health and productivity fed diets containing grains such as wheat, rye, barley and oats (Basmacioglu et al, 2010). Many studies have shown that an appropriate exogenous enzyme product supplemented to wheat-based diets removed anti-nutritional factors from feeds, reduced intestinal viscosity, increased nutrients digestibility, and resulted in a better feed efficiency in broilers (Wang et al, 2005;Basmacioglu et al, 2010). Therefore, the following study was designed to study the effect of different levels of wheat screenings with or without a blend enzyme on performance, carcass characteristics, gastrointestinal parameters, serum lipid metabolites, and jejunal histomorphology of finisher broilers.…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation